Poller blocking screw augmentation to treat delayed union of proximal tibial shaft fracture after locked IM nailing. - Ferreli, Alberto; Nonne, Daniela; Russo, Angelo; Dessì, Giuseppe; Marongiu, Giuseppe (Acta Biomedica Atenei Parmensis, 2021)
Cases: We present the cases of two adult male patients with painfully delayed union of proximal tibia diaphyseal fracture after intramedullary nailing. Patients underwent to nail dynamization and Poller blocking screw augmentation at 3 and 5 month, respectively, after the index surgery. Both patients were pain-free after the surgery and bone-union were radiographically evident after 3 months. At 12-month follow-up, patients returned to their previous activities. Conclusions: Although nail dynamization is the choice treatment to obtain fracture compression for delayed union of tibial shaft fractures, augmentation with Poller blocking screw could provide additional mechanical stiffness in unstable supra-isthmic shaft fractures of the tibia and favour bone union.